THE PROCESS OF DEVELOPING STUDENTS' LEARNING ACTIVITIES THROUGH THE APPLICATION OF FUN LEARNING METHOD AT AN-NUR SDI (PIONIR: JURNAL PENDIDIKAN, 2025)
With the development of the increasingly advanced era, teachers are required to be able to create fun learning for students. Boredom in learning is a factor that inhibits learning for students. Learning using the fun learning method is a fun method for students, fun learning fosters enthusiasm for learning. SDI An-Nur innovates learning methods to be fun and not boring. The method used is a descriptive method with a qualitative approach. Data was collected through observation, interviews, and documentation. The purpose of this study was to prepare for the implementation of the fun learning method, support and challenges in implementing the I fun learning method, and for learning process activities using the fun learning method. Based on the results of the study, it can be seen that the implementation of the fun learning method at SDI An-Nur has been going quite well. Teachers are able to prepare a structured learning implementation plan, use fun learning methods, compile learning models, utilize creative learning media and compile evaluations according to student potential. Although there is an impact in using the fun learning method, it is an involvement of students in learning. However, the implementation of the fun learning method is in accordance with the needs of students in learning.Keywords: fun learning method, Implementation of learning, Learning activities using the fun learning method